Host-intestinal microbiota mutualism: "learning on the fly". - Erkosar, B.; Storelli, G.; Defaye, A.; Leulier, F. (Cell Host & Microbe, 2013)
Given the complexity of the mammalian microbiota, there is a need for simple models to decipher the effector and regulatory mechanisms underlying host/microbiota mutualism. Approaches using Drosophila and its simple microbiota carry the potential to unravel the evolutionarily conserved mechanisms engaged in this association. Here, we review recent work carried out in this model, providing insights and exciting perspectives.